Sustainability of fertigation in agricultural crop production by IoT system: A review - Nur Syahirah, Mohd Sabli; Mohd Faizal, Jamlos; Fatimah, Dzaharudin (Springer, 2021)
The increasing of world population over the year lead to an exponential 8 in food demanding which is the main cause towards precision agriculture. Sus-9 tainability of agriculture production is an emerging and fascinating field of IoT, 10 predictive analytics and classifier research. It helps farmers to enrich their ferti-11 gation business and support growth of local economy. This review describes a 12 review of an integrated research field on fertigation technique, IoT roles with 13 various communication protocols in agriculture. Interestingly, (i) Agricultural 14 crop with fertigation technique required different parameter to monitor e.g. elec-15 trical conductor (EC), Total dissolve solid (TDS) for different crops compared to 16 normal irrigation and (ii) Different size of farm need different type of wireless 17 communication protocol. It reveals that crops with fertigation technology ad-18 vancement like IoT capable to sustain the productions even tough in adverse en-19 vironmental conditions.